Hypophosphataemia with non-tenofovir-containing antiretroviral therapy. (July 2013) - Wainwright, E; Sherrard, J; Duncan, S; Shine, B; Dorrell, L
Summary: Hypophosphataemia with tenofovir (TDF) treatment has been well described. The role of HIV infection and of other antiretroviral (ART) agents in hypophosphataemia has received less attention. The aim of this study was to determine the prevalence of hypophosphataemia in HIV-positive adults. We measured the fasting plasma phosphate level and estimated glomerular filtration rate (eGFR) in 123 HIV-positive patients. A total of 26% had hypophosphataemia and 11% had hypophosphataemia of grades 2–4 (0.65 mmol/L or less). Hypophosphataemia of any grade was more frequent in those who were ART-treated than ART-naive (35% versus 10%; P = 0.0001). Multiple linear regression analysis showed no significant association between phosphate level and gender, TDF status, duration of ART, duration of HIV infection and eGFR. Increasing age was significantly associated with a very small rise in phosphate level. Isolated hypophosphataemia was significantly more frequent in HIV-positive subjects receiving ART than ART-naive individuals, irrespective of the drug regimen.